Analgesic effect of honey bioactive compounds and its role in reducing morphine tolerance - Nur Husna Zakaria, Nor Zidah Ahmad, Siti Norhajah Hashim, Liyana Hazwani Mohd Adnan, Mohamad Halim Mohamad Shariff, Nasir Mohamad, Khairi Che Mat, Nor Hidayah Abu Bakar (Journal of Applied Pharmaceutical Science, 2015)
Honey has been used as a supplement nutrient in human for centuries. It exerts antibacterial, anticancer, anti-inflammatory properties as well as analgesic activity. But not many studies have been done to analyze effect of honey on morphine tolerance. Hence, this review is targeting on analgesic effect of honey bioactive compounds and their potential in morphine tolerance study.
Keywords: Honey, bioactive compound, analgesic , morphine tolerance.